MUSCULOSKELETAL PAIN AMONG UNDERGRADUATE PHYSICAL THERAPY STUDENTS: SINGLE CENTERED SURVEY - Komal Nadeem; Zunaira Mehdi; Samreen Sadiq; Hafiz Muhammad Asim (ziauddin University, 2024)
Background: Musculoskeletal discomfort not related by a syndrome is very communal in juvenile and puberty getting lifetime prevalence as great as 40%. It affects student's quality of life and their productivity in education. So, the main objective of current study was to access musculoskeletal pain among undergraduate physical therapy students. Methods: A Descriptive type of cross sectional survey was conducted at Lahore Medical and Dental College (LM&DC) for duration of almost six months from April 2018 to October 2018. Sample size recruited was 321 physical therapy students and they were included according to inclusion exclusion criteria. Assessment of Musculoskeletal pain was done using Nordic musculoskeletal questionnaire. An analysis was done using SPSS 21. Results: The findings showed that musculoskeletal pain among students was most commonly prevalent in lower back region constituting 65.4% (n = 210) followed by upper back 53.9% (n = 173) and neck region 48.6% (n = 156). Conclusion: Musculoskeletal pain was highly prevalent among medical students and most commonly found in lower back region.